Metal Hydroxide Precipitation from Wastewater - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2022)
This Excel workbook uses 9 worksheets to make calculations for metal precipitation from wastewater. In the first worksheet, there is provision for user entry of the concentration of each of seven metals (zinc, nickel, chrome, copper, cadmium, lead, and iron) in the wastewater. There is also provision for user entry of the design pH and a safety factor for the calculations as well as selection between caustic or lime as the chemical to be used for the precipitation and specification of the concentration of the caustic or lime solution being used. Worksheets 2 through 8 each make calculations for one of the metals. Solubility vs. pH data for each of the metals is used to generate an equation for the solubility of that metal as a function of pH, then the equilibrium values are calculated for the metal removal rate, effluent metal concentration, solids production rate, and chemical usage rate. The last worksheet provides a summary of the calculated results for each of the metals.